Higher education decision making of Australian women with caring responsibilities - Munro, Deborah; Willis, Jill; Gibson, Andrew; Laundon, Melinda (Frontiers in Education, 2023)
It is well established that women have greater caring responsibilities than men, however, little is known about how this care work influences the decision-making processes of female carers who are considering higher education (HE). These deliberations occur well before women commit to enrolling, with the result that carers may make decisions to delay or not pursue HE, with consequences for their own careers and the persistence of gender equalities more broadly. While this review of academic literature published since 1980 in Australia shows that very little is known about how women who have caring responsibilities make decisions about whether or not to undertake HE studies, important issues are identified. Carer is most often defined in terms of who is being cared for, highlighting intersections of responsibilities. Insights from the studies about what enables and constrains women with caring responsibilities in HE show a complex array of personal, social and cultural concerns that can influence decisions. New decision-making theories are therefore needed that will encompass the role of contexts and care in decisions. The paucity of research points to an urgent need for studies which will address the gaps in knowledge regarding the decision-making processes female carers undertake prior to enrolment, with this review providing some advice meanwhile to inform career practitioners, HE providers and career researchers.